Chapter I dolori del giovane Čechov. Considerazioni filologiche sui racconti giovanili - Ghini, Giuseppe (Biblioteca di Studi Slavistici, 2019)
The article addresses textual decisions made by Čechov's editors in publishing his early short stories. We demonstrate that choices made by other editors and translators has depended crucially on the configuration of his texts found in academic editions of Čechov's Complete Works. Specifically, in the volumes that these editions devote to the young Čechov, editors place what are in fact the first versions of these short stories in the critical appendix, while furnishing as the featured examples of these texts' versions that Čechov had reviewed and retouched for collections published during his lifetime. As a result, works of the "young Čechov" are often actually works of the "mature Čechov", a situation that has led to a worldwide misunderstanding.